Web Based Locker Booking System with Multifactor Authentication for Wajasakti Sdn Bhd - Radin Nur Haziqah Radin Abdul Aziz; Khairul Amin Bin Mohamad Sukri (Applied Information Technology And Computer Science, 2024)
E-Locker Booking System with Multifactor Authentication for Wajasakti Sdn Bhd is a system that allow their employee to book a locker to keep their belonging safe which located in their workspace. Since they only use logbooks to keep track of all the information, recordings occasionally stop existing and disappears and having several disorganised records which give time-consuming to search down the data of employees. This paper proposes a locker booking system that enables workers to reserve lockers while assisting administrators in managing reservations and workers’ data. The Agile technique is being used for this project methodology to develop systems to be more effective because all needs and deliverables are better understood. As a result, the development of the locker booking system has been completed successfully by using HTML, CSS, JavaScript and PHP languages. The system has nine modules which include Login Module, Register Module, Booking Locker Module, Manage Booking Record Module, Manage Locker Module, Manage Admin Module, Manage User Module, Report Analysis Module, and Activity Log Module. The project is successful with that the security features of the system would be recognised for their efficacy. Thus, this system give effective management to the admin as it makes it possible for administrators to monitor locker availability, usage, and demand-based locker distribution. This reduces the possibility of conflict or double bookings and guarantees effective locker utilisation